Day 3 Thu, October 26, 2017 2017
DOI: 10.4043/28034-ms
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Strategy Minimizes Lost Circulation Non-Productive Time in Brazilian Deep Water Pre-Salt

Abstract: Fluid losses are still today one of the most challenging problems in well construction. The scenarios faced by operators during development and exploratory campaigns in the deep water pre-salt area are characterized by natural fractures, vugs and caves. Therefore, problems related to loss of circulation are critical, increasing the non-productive time and consequently, well construction costs. Additionally, in several situations, conventional drilling limitations prevent the reaching of the well target. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Toreifi et al [36] identified the advantages of the SVM algorithm in comparison with multi-layer perceptron (MLP) for prediction of loss events in fractured formations. Cristofaro et al [37] implemented several machine learning algorithms to classify the success in applying different LCMs in a deep-water pre-salt basin offshore Brazil. They showed that by combining neural networks with an instance-based algorithm better prediction performance could be achieved.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…Toreifi et al [36] identified the advantages of the SVM algorithm in comparison with multi-layer perceptron (MLP) for prediction of loss events in fractured formations. Cristofaro et al [37] implemented several machine learning algorithms to classify the success in applying different LCMs in a deep-water pre-salt basin offshore Brazil. They showed that by combining neural networks with an instance-based algorithm better prediction performance could be achieved.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…Therefore, it is arduous to predict. Therefore, many researchers applied the artificial intelligence to solve problems related to lost circulation such as Anifowose et al [32], Castillo [33], Moazzeni et al [34], Toreifi et al [35], Efendiyev et al [36], Far and Hosseini [37], Solomon et al [38], Manshad et al [39], Al-Hameedi et al [40], Alkinani et al [41], Abbas et al [42], Cristofaro et al [43], and Jahanbakhshi and Keshavarzi [44]. All these studies applied a single technique of AI to predict either the type of losses, the amount of losses, or the loss treatment, besides using many input parameters that are difficult to access in every well.…”
Section: Functional Network (Fn)mentioning
confidence: 99%
“…Lost circulation estimation is a limited topic in the literature; only a few papers were published about this topic. Some shortcomings were identified in the previous work as follows [34,36,[39][40][41][42]]:…”
Section: To Prohibit the Development Of New Fractures That Maymentioning
confidence: 99%
“…Collected data from the literature Al-Azani et al [31] Elkatatny et al [32],Abdelgawad et al [33] Drilling fluid rheological properties Estimating rheological properties of drilling fluid Cristofaro et al [34] Mud loss Used multiple artificial intelligence methods to find the best treatment for mud losses Hoffimann et al [35] Drilling reports sentence classifications Used ANNs to develop a methodology for automating sentences in drilling reports Li et al [36] Lost circulation Used ANNs to predict lost circulation risk during drilling Al-AbdulJabbar et al [37] Formation top prediction while drilling Used ANNs to predict formation tops while drilling Elzenary et al [38] Equivalent circulation density (ECD) prediction Used ANNs to predict ECD while drilling used to verify the model, and testing data are used to test the network and assess the outcomes. Feedforward backpropagation is the process where the data are imported to the model and obtaining a desired output, then the output of the network will be compared with the actual output, the error will backpropagate, and the weights are adjusted until calibration is reached.…”
Section: Feedforward Backpropagationmentioning
confidence: 99%